Effects of e-cigarette use on oral health: literature review (Research, Society and Development, 2022)
Electronic cigarettes are devices capable of producing aerosols by heating a liquid that may or may not contain nicotine. Thus, this literature review aims to point out the effects caused by electronic cigarettes on oral health, identifying your damage and your relationship with the development of oral pathologies, as xerostomia, irritation, sensitivity, burning, nicotinic stomatitis, hairy tongue, bad breath, cheilitis, delayed healing, as well as leukoplakia and squamous cell carcinoma. Addressing from toxicity to trauma injuries. It is noticed that, in the long term, the use of electronic devices can cause periodontal diseases, tooth cavity and oral infections. This may impair the functionality and aesthetics of the stomatognathic system. For this reason, monitoring by the dentist is essential in the care and prevention guidelines than the possible damage of electronic cigarettes cause to the oral environment.